Physiological Response of Shallow-Water Hard Coral Acropora digitifera to Heat Stress via Fatty Acid Composition - Safuan, Che Din Mohd; Samshuri, Muhammad Arif; Jaafar, Siti Nurtahirah; Tan, Chun Hong; Bachok, Zainudin (Frontiers in Marine Science, 2021)
Heat stress disturbs the mutualistic relationship between the hard corals and the symbiotic algae, which cause coral bleaching. A wide array of biochemical parameters is used to demonstrate the phenomenon. This study exposed a shallow-water hard coral, Acropora digitifera, to a series of elevated temperatures over time while the interaction between Symbiodiniaceae (SD) density, antioxidants activities, fatty acid (FA) composition, and putative FA health indicators was evaluated. Heat stress caused a substantial loss in SD densities, consequently regulated the antioxidant activities and caused significant changes in FA composition. There was a lack of evidence showing A. digitifera experienced oxidative stress; nonetheless, a significant decrease of monounsaturated fatty acid as (MUFA) and polyunsaturated fatty acid (PUFA) during the thermally induced experiment demonstrated that corals utilize their unsaturated FA as a final barrier or as a repair system against oxidative damage once the antioxidant enzyme cannot cope with stress condition. The lower ratio of putative FA health indicators [i.e., n-3 LC:n-6 LC, eicosapentaenoic acid (EPA):arachidonic acid (ARA), and docosahexaenoic acid (DHA):ARA] characterized an unhealthy coral. The loss of SD density was significantly correlated with certain PUFA markers [i.e., linolenic acid (18:3n6), 20:5n3, and 22:6n3] and putative FA health indicator (i.e., n-3 LC:n-6 LC, EPA:ARA, and DHA:ARA). These notably imply that the FA linked with the symbiont can be a potential health indicator for assessing the effect of the environmental stressor on coral. This study also revealed the regulation of FAs during stress conditions, especially when heterotrophic feeding is limited. Future studies on FA profiles toward antagonistic or synergistic effects will offer a better understanding of the nature of this relationship under a harsh climate.